Peran Etika Profesional dalam Membangun dan Meningkatkan Kepercayaan Publik terhadap Penegak Hukum di Indonesia - Iman Frijal Buanakhe; Indah Erdasari; Setyo Utomo; Sutiyani (AHKAM, 2026)
Public trust is an important indicator of the success of a law enforcement system in a state governed by the rule of law. However, various ethical violations by law enforcement officials, such as abuse of authority, corruption, discrimination in service delivery, and actions contrary to the principles of professionalism, have diminished public trust in law enforcement institutions and demonstrated a gap between the ideal standards of the legal profession and their implementation. This study aims to analyze the role of professional ethics in building and enhancing public trust in law enforcement authorities and to identify the factors influencing the effectiveness of legal professional ethics implementation in Indonesia. The study employed a qualitative method with a normative juridical approach supported by case studies and literature analysis. Data were obtained through a review of laws and regulations, professional codes of ethics for law enforcement officials, books, scholarly journal articles, and various cases of ethical violations and were subsequently analyzed descriptively and qualitatively. The results indicate that the consistent application of professional ethics plays an important role in strengthening the legitimacy of law enforcement institutions, improving the quality of public services, and ensuring legal certainty. Conversely, ethical violations that are not addressed transparently can reduce public trust and weaken the rule of law. This study affirms that strengthening oversight systems, providing continuous ethics education, and imposing firm sanctions are prerequisites for professional and integrity-based law enforcement. These findings contribute to the development of legal professional ethics scholarship and provide practical implications for law enforcement institutions in strengthening accountability, transparency, and public trust.